Life cycle assessment and structural evaluation of sustainable and cost effective engineered cementitious composite (ECC) repair mortars - George, Mareena; Sathyan, Dhanya (Frontiers in Built Environment, 2026)
This study presents a comprehensive evaluation of a sustainable Engineered Cementitious Composite (ECC) repair mortar developed using eco-efficient material modifications and its performance in rehabilitating partially distressed reinforced concrete (RC) beams. The environmental performance of the developed ECC was assessed through Life Cycle Assessment (LCA) using the ReCiPe 2016 Endpoint (H) method, considering a cradle-to-gate system boundary. The incorporation of quarry dust powder, supplementary cementitious materials (GGBS and silica fume), polymer modifiers (SBR latex), internal curing agent Polyethylene glycol (PEG), and hybrid fibres significantly reduced the overall environmental impact and cost compared to conventional mixes containing silica sand and PVA fibres. To validate structural performance, RC beams were cast and subjected to flexural testing after simulated distress and repair and compared with commercially available repair mortar. The ECC-repaired beams exhibited improved load-carrying capacity, ductility, and crack control relative to beams repaired with conventional mortars. The combined LCA and experimental results confirm that the optimized ECC mortar offers a balanced solution for sustainable and durable repair applications in RC structures.